2010
DOI: 10.1590/s1984-29612010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthelmintic activity of liquid waste of Agave sisalana (sisal) in goats

Abstract: It was evaluated the anthelmintic activity of Agave sisalana (sisal) juice against gastrointestinal nematodes and its potential toxic effects in goats. In vitro tests showed more than 95% reduction in larval counts of the genus Haemonchus spp. at concentrations between 86.5 and 146.3 mg.mL -1. In vivo the percent reduction of larvae of the fourth (L4) and fifth (L5) stages of Haemonchus, Oesophagostomum and Trichostrongylus was less than 95% in groups GI and GII, and between 80 and 90% in group GIII. A. sisala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…The substances contained in A. indica affect parasite feeding, growth, longevity, and fertility -interfering with copulation behavior, oviposition, and egg viability (El-Shafie and Basedow, 2003;Hasan and Ansari, 2011). The antihelminthic effect of Agave sisalana was studied in goats (Domingues et al, 2010;Botura et al, 2011;Silveira et al, 2012) and sheep (Silveira et al, 2012) but these studies showed discordant results. Agave sisalana contains saponins as secondary metabolites (Francis et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The substances contained in A. indica affect parasite feeding, growth, longevity, and fertility -interfering with copulation behavior, oviposition, and egg viability (El-Shafie and Basedow, 2003;Hasan and Ansari, 2011). The antihelminthic effect of Agave sisalana was studied in goats (Domingues et al, 2010;Botura et al, 2011;Silveira et al, 2012) and sheep (Silveira et al, 2012) but these studies showed discordant results. Agave sisalana contains saponins as secondary metabolites (Francis et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Only the hydroalcoholic extracts of Eugenia uniflora (Hassum et al, 2013;Gonçalves et al, 2016;Sprenger et al, 2016) and Artemisia annua Maciel et al, 2006;Krychak-Furtado et al, 2011), chloroform (Assis et al, 2003Maciel et al, 2006), acetone (Oliveira et al, 2011), dimethyl sulfoxide (Cunha et al, 2014, and dichloromethane (Cala et al, 2014) have been used as extractive agents. Other forms of plant preparation used to evaluate the anthelmintic effect in small ruminants were: i) dehydrated leaves (Parra et al, 2011;Gregory et al, 2015) and ground (Falbo et al, 2008) and ii) dehydrated and ground fruit (Falbo et al, 2008) and juices (Almeida et al, 2004;Domingues et al, 2010;Santos et al, 2011). Using in natura plants, only Curcubita pepol showed an RFEC above 80% (Almeida et al, 2007).…”
Section: Forms Of Plants For Use As Anthelminticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculated plants were grown for 4 months with daily irrigation in a greenhouse located at the Federal University of Recôncavo da Bahia (UFRB), Cruz das Almas campus. After this period, the R. similis juveniles were extracted from the banana roots according to the method described by Coolen and D'Herde (1972) and Jenkins (1964). The aqueous suspension of R. similis juveniles was counted in a Peters chamber under a microscope, and the suspension was adjusted to 150 juveniles per mL by dilution with sterile distilled water.…”
Section: R Similis Inoculum Preparationmentioning
confidence: 99%
“…Plants belonging to the genera Agave have reportedly shown biocidal activity against nematodes from goats and lambs (Botura et al 2011;Domingues et al 2010;Silveira et al 2012). Sisal liquid residue is composed of secondary metabolites such as alkaloids, phenolic compounds, glycosidic saponins, flavonoids, and tannins (Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%